The taxonomic status of some spiny-backed treefrogs, genus Osteocephalus (Amphibia: Anura: Hylidae) - Jungfer, Karl-Heinz (Zootaxa, 2010)
A reassessment of some Amazonian spiny-backed treefrogs (Osteocephalus) either considered to be junior synonyms or not associated yet with Osteocephalus reveals that O. cabrerai (Cochran and Goin, 1970) from lowland Colombia and Peru is distinct from a frog previously used to revalidate the species, that O. festae (Peracca, 1904) is a valid species from the foothills of the Andes in Ecuador, and that Hyla inframaculata Boulenger, 1882, from the lower Amazon in Brazil, is a member of this genus. The oldest available name for O. elkejungingerae (Henle, 1981) from the Andean foothills in Peru is O. mimeticus (Melin, 1941). Another Melin (1941) species, Hyla vilarsi from the Rio Negro watershed in Brazil, is also an Osteocephalus revalidated from the synonymies of several other frogs.